The Effect of Virtual Reality Gaming on Developing Computational Thinking Skills - Sukirman, Sukirman; Ibharim, Laili Farhana Md; Said, Che Soh; Murtiyasa, Budi (AI Society & STMIK Indonesia, 2024)
In the digital age, where programming prowess is increasingly crucial, the enhancement of Computational Thinking (CT) skills becomes essential. This study ventures into the scarcely explored domain of leveraging game-based learning (GBL) within virtual reality (VR) settings to bolster CT skills. Specifically, it introduces